PROBLEMATIKA RISK AND RETURN DALAM PERBANKAN SYARIAH - Afriyandi, Yuli (AS-SALAM, 2013)
The knowledge about risk in an investation is the important thing. Decisionof investaion for the investor is regarded the era that will come is unclear,it is contains a risk for inverstor. In order that in Islamic perspective, basicinvestation that needs to know in the institution of Islamic inance syariahsuch as bank that also place to invest fund. In the system of Islamic economy,ionvestation can decrease the poverty and increase the income with away to bene it the wealth productively. The investation activity whichagrees with Islamic syariah is the effort to produce the better life (falah),giving the bene its (maslahah) and keeping away the way of forbiddeninvestation, that is riba, gharar, and maysir. But, productive investation canbe implemented with the cooperation and proffessional in doing the mainprinciple of syariat.The control of risk in banking industry is the main part for investor to invest.The management of this risk includes identi icating risk, measuring risk,managing risk, limiting risk, and observing risk. Through this approachthe risk and the taking advantange can be measured. So the investorwill get the chance return or value of sharing resulit optimally and alsoprospectively. The indeterminancy level of risk and return of result are thechallenge its self to the syariah banking. The validity of law âhish risk bringsabout high returnâforces syariah banking to apply the manage the risk thatis more superior from conventional banking. So that the syariah bankingmust create a team that is able to manage and that is the include of themenegement of risk its self.Keywords: risk and return, investation, Sharia Banking